Infestation and Reproduction of Varroa destructor Anderson and Trueman and Hygienic Behavior in Colonies of Apis mellifera L. (Africanized Honeybee) with Queens of Different Genetic Origins - Schafaschek, Tânia Patrícia; Rodrigues Hickel, Eduardo; Lopes de Oliveira, Carlos Antonio; de Alencar Arnaut de Toledo, Vagner (Sociobiology, 2019)
The hygienic behavior and variables related to the varroa mite in Apis mellifera colonies, with queens of different origins, were evaluated from October 2013 to June 2014. Queens from the selection program of the Maringá State University (Maringá / PR), from a beekeeper/ producer of Santa Terezinha/ SC and unselected queens, randomly selected in an experimental apiary (Irineópolis / SC) were evaluated. Colonies with queens of Maringá presented an increase in the invasion rate and total reproduction of varroa as there was reduction of hygienic behavior. This group presented a reduction in the effective reproduction of the mite, with a mean of 2.3 fertile offspring. Colonies with queens of Santa Terezinha presented an increase in the invasion rate due to the reduction of hygienic behavior, but in a less marked manner, since this characteristic remained stable, with an average of 92.0%. The total and effective reproduction of the mite for this group was 1.7 and 0.9 of total and fertile offspring, respectively. Colonies with queens of Irineópolis showed the lowest hygienic behavior (78.0%) and the highest total (12.6) and effective (5.3) reproduction of the mite. The use of selected queens, with hygienic behavior, interferes with the varroa population dynamics, contributing to the reduction of the invasion and total and effective reproduction rates of the mite.